The role of economic factors, including the level of tuition, in individual university participation decisions in Canada - Johnson, David R.; Rahman, Fiona T. (Canadian Journal of Higher Education, 2005)
The study uses individual data from the Canadian Labour Force Survey to consider economic factors in university participation decisions by persons aged 17-24 from 1976 to 2003. The level of real tuition is one economic factor that may affect the university participation decision. There is also regional variation in the opportunity cost of university attendance; in the reduction in the probability of unemployment after obtaining a university degree; and in the proportion of university budgets used for financial support of students. In addition, there is some national variation by gender and over time in the return to a university education. This study finds that higher tuition levels in the 1990s did reduce the probability of university participation by persons aged 17,18 or 19 relative to a province- specific trend increase in university participation. Before drawing a policy conclusion from this result, it would be necessary to consider what the trend terms represent in the university participation decision.